Analysis of Biophilic Architecture Concepts Application in the Kebun Pak Budi Edu-tourism Building - Musthafa, Rahmat Nur (International Journal of Built Environment and Scientific Research, 2024)
Modern urban development focuses on urban areas, but the principles of urban development should be implemented in urban development, ensuring that new urban objects can be developed. These principles include economic growth, environmental conditions, community support, and technology implementation. Urban areas based on education should be developed in urban areas, such as Purwosari, to provide a unique atmosphere. However, the concept of biofilic, based on space and facilities, is also important. The "Kebun Pak Budi" urban area in Purwosari aims to develop the potential of urban areas by utilizing existing facilities. Biofilic concepts can help maintain the conditions of use, such as reducing stress and reducing water pollution, through long-term interaction with the environment, education, and research. The application of biofilic in urban areas can lead to positive environmental benefits, such as natural ventilation and dynamic communication.